Penerjemahan Novel Dracula Karya Bram Stoker dari Bahasa Inggris ke Dalam Bahasa Indonesia: Kasus Pengalihan Skema Budaya Divergen - Jaya, Doni (Paradigma: Jurnal Kajian Budaya, 2020)
Divergent cultural schema (DCS) is a collection of cultural knowledge required to interpret a text, which is assumed to be present in source readers (SR) but absent in target readers (TR). DCS typically takes the form of a highly concise source text without any sufficient information, so the translator applied various strategies. Bram Stoker’s Dracula, consisting of its English source text (ST) and Indonesian target text (TT), was chosen as data source due to its strong Victorian-European setting which contains many potential DCS. Data analysis generated several categories of results. The first is units of analysis (n = 758) which are classified into various schemata (n = 21) and subschemata (n = 84) based on certain similarity in schematic characteristics. The second is various types of ST divergence (n = 13). The third is the reasons for applying domesticating (n = 16) or foreignizing (n = 12) strategies, as well as their weaknesses (n = 20). The fourth is domestication as the dominant translation ideology. The fifth is a number of interesting phenomena (n = 25) related to the transfer of DCS such as ideological level, different levels of divergence among TR, and “foreignization” and “domestication” by ST writer. This research demonstrates the complexity of strategy applications and ideological positions which are dependent on many factors such as narrative context, linguistic constraints, ST divergence, or TR schemata.